2021
DOI: 10.1186/s13023-021-02062-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low-dose calcipotriol ointment on wound healing, pruritus and pain in patients with dystrophic epidermolysis bullosa: A randomized, double-blind, placebo-controlled trial

Abstract: Background Wound management is a critical factor when treating patients with the inherited skin fragility disease dystrophic epidermolysis bullosa (DEB). Due to genetic defects in structural proteins, skin and mucous epithelia are prone to blistering and chronic wounding upon minor trauma. Furthermore, these wounds are commonly associated with excessive pruritus and predispose to the development of life-threatening squamous cell carcinomas, underscoring the unmet need for new therapeutic option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A double-blind RCT is currently in place to evaluate the role of low-dose topical calcipotriol ointment on improving wound healing in DEB. 58 This is based on the antiproliferative role of calcipotriol on keratinocytes.…”
Section: Managementmentioning
confidence: 99%
“…A double-blind RCT is currently in place to evaluate the role of low-dose topical calcipotriol ointment on improving wound healing in DEB. 58 This is based on the antiproliferative role of calcipotriol on keratinocytes.…”
Section: Managementmentioning
confidence: 99%
“…As illustrated in Figure 5A, the Shik group mice were treated with Shik ointment on a daily basis, and GelMa and Shik-Fe were used every other week due to the sustained drug release from hydrogels. 37 In the current study, instead of the traditional daily dosing, 38 material dosing was administered once every 7 days, which could ease the clinical utilization and reduced the dose of the drug in general. Also, calculated in the dose, the Shik-Fe administration was ∼250 μg per tropical application, fully compatible to the clinical utilization dose.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Few clinical trials in EB have evaluated pruritus as a primary or secondary outcome. Studies of mesenchymal stromal cell infusions in RDEB have demonstrated reduced itch as a secondary endpoint [ 33 35 ] and a recent randomised, double-blind, placebo-controlled trial of calcipotriol in DEB wounds found a statistically significant fall in itch scores [ 36 ]. Another phase 2 randomised, double-blind, placebo-controlled trial of the neurokinin 1 receptor antagonist, serlopitant, included itch reduction as a primary endpoint in different types of EB; although not reaching statistical significance, results showed a trend for greater itch score reduction in the treatment arm [ 17 ].…”
Section: Discussionmentioning
confidence: 99%